Study on Binocular Accommodative Function in Children With Different Types of Intermittent Exotropia - Dan Li; Kun-Ling Li; Jing Wang; Lin-Lin Du; Li Li (Frontiers Media S.A., 2021)
Objective: This study aims to investigate the monocular and binocular accommodative amplitude (AMP) and accommodative function (AF) in children with different types of intermittent exotropia (IXT).Methods: A total of 40 children with IXT were enrolled in the study. Monocular and binocular AMP and AF were measured using the modified approach method and the ±2D flip method, and the differences between the fixing and non-fixing eyes of non-strabismic children and children with different types of IXT were compared.Results: The AMP of the fixing eyes of children with IXT was lower than that of their non-fixing eyes (p = 0.007). Conversely, the AF was higher in the fixing eyes than in the non-fixing eyes (p < 0.001). The AMPs of each group of children with IXT were lower than those of the control group, while the AMP of the group with convergence insufficiency was lower than that of the other two groups with IXT. In addition, the AF of the group with convergence insufficiency was lower than that of the group with basic exotropia and the control group (p < 0.05).Conclusion: There is a difference in accommodation between the fixing and non-fixing eyes of children with IXT, and the degree of variation depends on the type of IXT. Moreover, the binocular accommodative function of children with IXT is lower than that of non-strabismic children.